275 POSTOPERATIVE COMPLICATIONS DO NOT AFFECT QUALITY OF LIFE AFTER ESOPHAGECTOMY. (14th September 2020) - Jezerskyte, E; Laarhoven, H; Sprangers, M; Eshuis, W; Hulshof, M; Berge Henegouwen, M; Gisbertz, S
Abstract:  : Despite the attempts to reduce postoperative complication incidence after esophageal cancer surgery, up to 60% of patients endure postoperative complications. These patients often have a reduced health related quality of life (HR-QoL) and it may also have a negative effect on long-term survival. The aim of this study is to investigate the difference in short- and long-term HR-QoL in patients with and without a complicated postoperative course. Methods: A retrospective comparative cohort study was performed with data from the Dutch Cancer Registry (IKNL) and QoL questionnaires from POCOP, a longitudinal patient reported outcomes study. All patients with esophageal and gastroesophageal junction (GEJ) cancer after an esophagectomy with or without neoadjuvant chemo(radio) therapy in the period of 2015–2018 were included. Exclusion criteria were palliative surgery, patients with a recurrence, reconstruction with a colonic or jejunal interposition, no reconstruction and emergency surgery. HR-QoL was investigated at baseline and at 3, 6, 9, 12, 18 and 24 months postoperatively between patients with and without complications following an esophagectomy. Results: A total of 486 patients were included: 270 with and 216 without postoperative complications. The majority of patients were male (79.8%) with a median age of 66 years (IQR 60–70.25). Significantly more patients had comorbidities in the group with postoperative complications (69.6% vs 57.3%, p = 0.001). A significant difference in HR-QoL over time was found between the two groups in "choked when swallowing" score (p = 0.028). Patients that endured postoperative complications reported more problems with choking when swallowing at 9 months follow-up (mean score 12.9 vs 8.4, p = 0.047). This difference was not clinically relevant with a mean score difference of 4.6 points. Conclusion: Postoperative complications do not significantly influence the short- and long-term HR-QoL in patients following an esophagectomy. Only one HR-QoL domain showed difference over time, however, this was not clinically relevant.